Nutriology, pharmacology and cardiovascular effects of common wild vegetables - Yuan, Shi-Min (Progress in Nutrition, 2019)
The wild vegetables are praised for their nutritional, health care and even medical values. Preliminary wild vegetable dishes, health care products have been developed and popular with people. However, the systematic analyses of the common wild vegetables are scanty, and in particular, the toxicological studies are neglected in some extent during the utilization of these plants. In this article, the nutritional, health care and even medical values of several common wild vegetables are reviewed. The results suggested that they are more nutritional than the common cultivated vegetables, and that the cardiovascular effects are usually attributable to their anti-oxidant properties. With regard to the dietary safety, toxicological studies have to be continued as well.